PERSEPSI DAN KEYAKINAN DIRI: FAKTOR PENENTU MINAT MAHASISWA FKIP UNTAN MENJADI GURU EKONOMI - Siti Nurhani, Siti Nurhani (Jurnal Edukasi Ekonomi, 2024)
This research aimed to determine: (1) the influence of perceptions of the teaching profession on student interest in becoming economics teachers among FKIP UNTAN Economic Education students, (2) the influence of Self-efficacy on student interest in becoming economics teachers, and (3) the combined influence of perceptions of the teaching profession and Self-efficacy on student interest. Using a quantitative approach and influence study, the research involved 142 respondents from the 2020, 2021, and 2022 cohorts of FKIP UNTAN Economic Education students. Multiple linear regression analysis was employed, with perceptions of the teaching profession (Xâ‚) and Self-efficacy (Xâ‚‚) as independent variables, and student interest in becoming an economics teacher (Y) as the dependent variable. The findings revealed: (1) perceptions of the teaching profession significantly influenced students' interest with a value of 0.737 and a t-test significance of 0.000 0.05; (2) Self-efficacy significantly influenced students' interest with a value of 0.663 and a t-test significance of 0.000 0.05; and (3) both variables significantly influenced students' interest simultaneously, with an Fcount value of 92.963, greater than the Ftable value of 3.06, and a significance level of 0.000 0.05.